The use of piezosurgery for mandibular third molar extraction - Tanasković Nenad; Lučić Miroslav (Stomatološki glasnik Srbije, 2014)
Introduction. Extraction of impacted mandibular third molars is often accompanied by intraoperative and postoperative complications such as damage of the inferior alveolar nerve, prolonged difficulty in mouth opening, alveolitis, pain and swelling in the region of surgery. The aim of this study was to compare two surgical techniques (standard and piezo) in the extraction of mandibular third molars and to assess their postoperative complications. Material and Methods. Study included 16 patients (8 male and 8 female) age 17 to 32 years treated in the period from 2012 to 2014. All patients had both mandibular molars impacted. One third molar was extracted using classical technique while the other one using a piezo device. Preoperative preparation was the same for all patients and included radiological analysis and verification of teeth by ortopan tomography (OPG) and CT. Patients were assessed one, seven and 14 days after the procedure. Results. After the extraction, all patients were followed for postoperative symptoms: pain, swelling and paresthesia of the inferior alveolar nerve. The results confirmed advantages of piezosurgery in the removal of impacted mandibular third molars. Average duration of the intervention was 18 minutes with standard technique while the duration with piezo technique was 23 minutes. According to the visual-analog scale (VAS) the average pain in the standard group was 9 whereas in the piezo group it was 6. Postoperative swelling was 10 mm (pronounced) the first day after the procedure in the standard group while in the piezo group it was 6 mm (moderate). Conclusion. The use of piezo technology for the extraction of impacted wisdom teeth is reliable method which reduces the risk of the most common postoperative complications following mandibular wisdom teeth removal.